1932
DOI: 10.1098/rspb.1932.0025
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the phosphagens, with some remarks on the origin of vertebrates

Abstract: The original discovery of labile phosphorus in muscular tissue by Eggleton and Eggleton (1927, a , b ) was rapidly followed by a succession of researches which demonstrated its great importance in muscular contraction. Fiske and Subbarow (1929) showed shortly afterwards that the phosphagen of the Eggletons was a compound containing equimolecular amounts of creatine and phosphoric acid, which, owing to its great instability in acid solution, had always previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

1933
1933
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Studies on other species point to the preEence of arginino phosphate in oyster muBcle (Meyerhof, 1928) nnd it proved possible to demonstrate this couipound iu both the nacreoua and vitreous tissue (Table 11) by methods involving phosphorus determination after fractionating the Ca salts (J. Needham, D. M. Noedham, Baldwin and Yudkin, 1932). These results were confirmed in other experiments by hydrolysing the Ca salt of arginine phosphate with 0-1 M IICl at 100' 0. and determining the arginino set free by using arginase to produce urea, wbieh eould be estimated maiiometrically with urease (Kreba, 1942).…”
Section: Presence Of Phospkagensupporting
confidence: 74%
“…Studies on other species point to the preEence of arginino phosphate in oyster muBcle (Meyerhof, 1928) nnd it proved possible to demonstrate this couipound iu both the nacreoua and vitreous tissue (Table 11) by methods involving phosphorus determination after fractionating the Ca salts (J. Needham, D. M. Noedham, Baldwin and Yudkin, 1932). These results were confirmed in other experiments by hydrolysing the Ca salt of arginine phosphate with 0-1 M IICl at 100' 0. and determining the arginino set free by using arginase to produce urea, wbieh eould be estimated maiiometrically with urease (Kreba, 1942).…”
Section: Presence Of Phospkagensupporting
confidence: 74%
“…As a result, in 1932, he was awarded the official fellowship of his college and honored with the Doctor of Science degree. Most important, just prior to his travel to Germany, in the spring of 1933, Needham was appointed Reader in Biochemistry, positioning him as second-in-command to Frederick G. Hopkins, the institute's renowned director (Cambridge University Registry, 1932;Needham, 1932Needham, , 1933a). Needham's esteemed stature and scientific prestige allowed him to recruit researchers and research students from abroad, thereby compensating for the limited interest shown by his colleagues.…”
Section: Team and Proceduresmentioning
confidence: 98%
“…11 9 The Needhams worked in different research fields but had collaborated on occasion since the early days of their respective careers. During the 1920s, they studied cellular oxidation-reduction processes and in the early 1930s, conducted research in comparative biochemistry (Needham and Needham, 1925;Needham et al, 1932;Teich, 2003;Armon, Interview with Mikula´sˇTeich, 17 May, 2006). 10 The embryological research existing was conducted primarily in the Oxford Zoological Department and to a large extent followed on the morphological tradition and its occupation with the relationship between evolution and development (Ridley, 1985;Horder, 2008).…”
Section: Team and Proceduresmentioning
confidence: 99%
“…About the time the Eggleton and Eggleton (1927) (2) and Fiske and Subbarow (1929) (3) discovered PCr in vertebrate skeletal muscle, Meyerhof and Lohmann (20) found another phosphagen, PArg, in crustacean muscle (4). Six years later, Lohmann demonstrated the reaction in muscle extracts prepared from crabs.…”
mentioning
confidence: 99%